The Heidelberg Circle of Jurists and its struggle against allied jurisdiction: amnesty-lobbyism and impunity-demands for National Socialist war criminals (1949-1955) - Glahé, Philipp (Journal of the history of international law, 2019)
Abstract After the Second World War, the Allies began a program of legal prosecution of war criminals who were to be sentenced in fair and public processes. However, these processes soon evoked vivid criticism, and by no means simply from former National Socialists. The Heidelberg Circle of Jurists (‘Heidelberger Juristenkreis’) is an example of a heterogeneous lobby group including victims of National Socialism as well as supporters of this ideology demanding amnesty for German war criminals between 1949 and 1955. Numbering forty high-ranking judges, lawyers, politicians, professors and church representatives, the Circle had access to a vast network and had a considerable impact on Allied and German war-crimes policy. On the basis of new source material, this article examines the Circle’s evolution, its apparently contradictory composition, its argumentation and its aims, by focusing on three of its members, the former minister of justice of the Weimar Republic and legal philosopher Gustav Radbruch, the internationalist Erich Kaufmann and the Nuremberg lawyer Hellmut Becker.
Gesehen am 21.09.2020